A Copper(I)-Mediated Tandem Three-Component Synthesis of 5-Allyl-1,2,3-triazoles - Song, Yoona; Lee, Soyun; Dutta, Palash; Ryu, Jae-Sang (Synthesis, 2020)
A copper(I)-mediated tandem three-component reaction using alkynes, azides, allyl iodides, CuI and NaNH2 is developed. The reactions proceed smoothly at room temperature to afford 5-allyl-1,2,3-triazoles, which can be further converted into 1,2,3-triazole-fused tricyclic scaffolds. This method features an efficient one-pot cascade route using commercial alkynes and affords the corresponding 5-allyl-1,2,3-triazoles with high yields and good selectivity under mild reaction conditions.
Keywords: 1,2,3-triazoles; multicomponent reactions; one-pot reactions; click reactions; copper catalyst